2009
DOI: 10.1021/bi801696n
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Directed Phosphorylation of the Dopamine Transporter N-Terminal Domain

Abstract: Phosphorylation of the dopamine transporter (DAT) on N-terminal serines and unidentified threonines occurs concomitantly with PKC-and substrate-induced alterations in transporter activity, subcellular distribution, and dopamine efflux, but the residues phosphorylated and identities of protein kinases and phosphatases involved are not known. As one approach to investigating these issues we recombinantly expressed the N-terminal tail of rat DAT (NDAT) and examined its phosphorylation and dephosphorylation proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 54 publications
6
92
0
Order By: Relevance
“…6 (Granas et al, 2003;Cervinski et al, 2005). Furthermore, in vitro phosphorylation experiments using purified PKC␣ to phosphorylate purified glutathione transferase (GST) fusion proteins containing the DAT N terminus have shown that this domain is a PKC substrate (Fog et al, 2006;Gorentla et al, 2009). However, additional PKC phosphorylation sites outside the N-terminal domain might exist in DAT.…”
Section: Phosphorylation a Protein Kinase C-mediated Phosphorylationmentioning
confidence: 99%
“…6 (Granas et al, 2003;Cervinski et al, 2005). Furthermore, in vitro phosphorylation experiments using purified PKC␣ to phosphorylate purified glutathione transferase (GST) fusion proteins containing the DAT N terminus have shown that this domain is a PKC substrate (Fog et al, 2006;Gorentla et al, 2009). However, additional PKC phosphorylation sites outside the N-terminal domain might exist in DAT.…”
Section: Phosphorylation a Protein Kinase C-mediated Phosphorylationmentioning
confidence: 99%
“…The DAT N terminus contains several threonine and serine residues that may be phosphorylated by protein kinase C (PKC), protein kinase A (PKA), protein kinase G, and Ca 2+ /calmodulin protein kinase II (Gorentla et al, 2009). Proline-directed phosphorylation of DAT threonine 53 may be involved in maintaining DAT transport (point mutations decrease DAT V max ) and may also be involved in amphetamine (AMPH)-induced reverse transport (Gorentla et al, 2009;Foster et al, 2012).…”
Section: B Dopamine Transporter Regulationmentioning
confidence: 99%
“…The DAT N terminus contains several threonine and serine residues that may be phosphorylated by protein kinase C (PKC), protein kinase A (PKA), protein kinase G, and Ca 2+ /calmodulin protein kinase II (Gorentla et al, 2009). Proline-directed phosphorylation of DAT threonine 53 may be involved in maintaining DAT transport (point mutations decrease DAT V max ) and may also be involved in amphetamine (AMPH)-induced reverse transport (Gorentla et al, 2009;Foster et al, 2012). Acute, in vitro activation of PKC by phorbol esters has been associated with a downregulation of DAT activity, which coincides with DAT phosphorylation and reduced plasma membrane expression (Copeland et al, 1996;Vaughan et al, 1997;Zhu et al, 1997;Daniels and Amara, 1999;Melikian and Buckley, 1999).…”
Section: B Dopamine Transporter Regulationmentioning
confidence: 99%
“…Cdk5 has been shown to increase phosphorylation of the recombinantly expressed DAT N-terminal tail (Gorentla et al, 2009). To determine whether the pharmacological actions of roscovitine on DAT activity we observed were Cdk5-mediated, we transfected YFP-HA-hDAT-PAE cells with Cdk5-siRNA.…”
mentioning
confidence: 99%